THE INFLUENCE OF LEADERSHIP STYLE, WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE AT THE SECRETARIAT OF DPRD RIAU ISLANDS PROVINCE - Aribowo, Kuncoro; Satriawan, Bambang; Gita Indrawan, Mohamad; Kusuma, Andhi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this study was to determine and analyze the effect of leadership style, work environment, work discipline on employee performance with work motivation as an intervening variable. The method used in this study is object observation, data collection using a questionnaire and distributed to 74 respondents. Statistical data analysis used SEM-PLS (Structural Equation Modeling-Partial Least Square) and used paths to examine patterns of relationships that reveal the influence of variables on other variables, both direct and indirect effects assisted by Smart PLS Ver 3.0 software. The results of the research in this study show that leadership style has a direct positive and significant effect on employee performance with a p-value of 0.024 <0.05,